Characterization and Cross-Sectional Modeling of the Newly Identified Rawup Fault Based on Relocated Hypocenters and Focal Mechanism in South Sulawesi - Kevin Hanyu Clinton Wulur; Joshua Purba; Ramadhan Priadi (Department of Physics, Sebelas Maret University, 2025)
This study presents an integrated seismotectonic analysis combining earthquake hypocenter relocation and P-wave polarity–based focal mechanism modeling to investigate the microseismic cluster in the Maros–Pangkep region, South Sulawesi. Using seismic data recorded by the BMKG network between 2019 and 2024, a total of 191 events were successfully relocated through the double-difference (HypoDD) algorithm, achieving a significant reduction in RMS residuals. The relocated hypocenters delineate a coherent northwest–southeast–trending fault plane with a strike of approximately 260° and a dip of 7–9°, consistent with a dextral strike-slip mechanism exhibiting minor oblique components. Integration with polarity-derived focal mechanisms confirms a consistent stress orientation compatible with regional compression along the Walanae Fault System. This alignment suggests the presence of a previously unmapped active structure, herein referred to as the Rawup Fault, accommodating local stress redistribution between carbonate and volcanic–clastic units. The findings advance the understanding of active deformation in low-seismicity, karst-dominated terrains and demonstrate the value of combining relocation and focal mechanism analyses for detecting hidden faults. These results provide new insights into the tectonic evolution and seismic hazard potential of the Maros-Pangkep.